Comparison of detailed experimental wavenumber spectra with gyrokinetic simulation aided by two-dimensional full-wave simulations. (31st March 2017) - Happel, T; Görler, T; Hennequin, P; Lechte, C; Bernert, M; Conway, G D; Freethy, S J; Honoré, C; Pinzón, J R; Stroth, U
Abstract: The importance of using a comprehensive suite of tools for the validation of a gyrokinetic code is described. This is detailed by presenting experimental wavenumber spectra which show pronounced differences, although they are measured at the same toroidal, poloidal and radial location. They are obtained via Doppler reflectometry and the differences are due to the probing beam polarization. These differences are reproduced convincingly using turbulence from a gyrokinetic simulation as input for two-dimensional full-wave simulation. It is demonstrated that the application of synthetic diagnostics is indispensable if non-trivial diagnostics are used in the experiment. Furthermore, the measurement of wavenumber spectra via Doppler reflectometry with X-mode probing beam polarization might be problematic due to nonlinear wave–plasma interactions and should be regarded with care when used for quantitative statements or the validation of gyrokinetic codes.